Рассказы - Тургенев Иван Сергеевич (Библиотека школьника, 2003)
Экземпляры: ф.1 (2003) / Инвентарный номер: 46479 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Т 87 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-4